Implementasi Smart Mining dan Teknologi Hijau dalam Mitigasi Dampak Pertambangan Nikel Terhadap Lingkungan di PT. Sulawesi Cahaya Mineral - Eko Prasetio, Bambang; Hasrianti, Hasrianti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In this case, we need to know about mining in Indonesia, our motherland has a lot of natural resources that can be renewed (renewable resources), for example rivers, forests, soil quality, and natural resources that cannot be renewed (non-renewable). resources) for example coal, petroleum and metals. There are positive and negative points in the mining industry in our country, in this case from a positive perspective, the mining industry contributes to Indonesia's national gross domestic product (GDP), opens up quite a lot of career/employment opportunities for local and non-local communities, infrastructure development, and improving the standard of living of the surrounding community. From a negative perspective, the mining industry is a scourge in terms of environmental damage, climate change, human rights violations and social inequality. In this case I will raise the topic of the impact of the nickel metal mine of PT, Sulawesi Cahaya Mineral, Routa area, Konawe Regency, Southeast Sulawesi Province on the environment.